Redefining the Reconstructive Ladder in Vulvoperineal Reconstruction: The Role of Pedicled Perforator Flaps - Elia, Jhonatan; Do, Nicholas T. K.; Chang, Tommy N.-J.; Lai, Chyong-Huey; Chou, Hung-Hsueh; Chang, Frank C.-S.; Huang, Jung-Ju (Journal of Reconstructive Microsurgery, 2021)
Background Gynecological reconstruction is difficult, particularly in cases with recurrence and received previous surgeries and/or radiotherapy and necessitate secondary reconstruction. Perforator flaps can preserve other donor sites for potential later reconstruction, and they also can be better tailored to the defect. We hypothesized that the use of perforator-based flaps can better restore the defect with less complications.Methods A retrospective review was conducted of all patients who underwent vulvar–perineum reconstruction between 2011 and 2018 by the senior author, and oncologic and reconstructive outcomes and complications were analyzed.Results Thirty-three patients underwent 55 soft tissue reconstructions for vulvar–perineum defects during the study period. The mean follow-up time was 27.6 ± 28.9 months. Squamous cell carcinoma was the most common cancer (45.5%). For 11 patients (33.3%), the procedures were performed for the treatment of recurrent cancer. The average defect size was 39.8 ± 34.3 cm2. The overall survival rate was 90.3%. Profunda artery perforator flaps were the most commonly applied flap for reconstruction in both the primary and recurrent groups. Poor wound healing was the most common complication which occurred in 10 of the 55 flaps (18.2%). Perforator flaps presented fewer complications than myocutaneous flaps or traditional random flaps. Similarly, Island pedicle flap design also presented fewer complications than traditional rotation flaps. With proper reconstruction, previous surgery or radiotherapy did not contribute to an increase in complications.Conclusion In our experience, perforator flaps can provide satisfactory reconstruction for perineum reconstruction with low postoperative complications while preserving other donor sites in the event of disease recurrence for repeat resection and reconstruction. Previous surgery or radiotherapy did not increase the complications or preclude its usage. A redefined reconstructive ladder was created to help selecting the best state-of-the-art technique for reconstruction to achieve better results.
Keywords: pedicle flap; perforator flap; pelvic exenteration reconstruction; perineum reconstruction; vulvar reconstruction